(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Plant substances with physiological activity have been used in medicine since time immemorial as effective medicines. It was found that many substances isolated from plants and playing an important role in their development and growth have IFN-inducing activity. These include purines, phenols and their derivatives (theophylline, caffeine, theobromine, tannin, etc.) [1].